Effect of the triazole ring in zinc porphyrin-fullerene dyads on the charge transfer processes in NiO-based devices. Issue 37 (17th September 2018) - Nikolaou, Vasilis; Plass, Fabian; Planchat, Aurélien; Charisiadis, Asterios; Charalambidis, Georgios; Angaridis, Panagiotis A.; Kahnt, Axel; Odobel, Fabrice; Coutsolelos, Athanassios G.
Abstract : Three covalently linked donor–acceptor zinc porphyrin–fullerene (ZnP–C60 ) dyads were tested as sensitizers in NiO-based dye-sensitized solar cells (DSCs). Abstract : Herein, the synthesis of three covalently linked donor–acceptor zinc porphyrin–fullerene (ZnP–C60 ) dyads (C60 tr ZnPCOOH, C60 tr ZnP tr COOH andC60 ZnPCOOH ) is described, and their application as sensitizers in NiO-based dye-sensitized solar cells (DSCs) is discussed. To the best of our knowledge, this is the first example where covalently linked ZnP–C60 dyads have been used as chromophores in NiO-based DSCs. In an effort to examine whether the distance of the chromophore from the electron acceptor entity and/or the NiO surface affects the performance of the cells, a triazole ring was introduced as a spacer between ZnP and the two peripheral units C60 and –COOH. The triazole ring was inserted between ZnP and C60 in dyadC60 tr ZnPCOOH, whereas both the anchoring group and C60 were connected to ZnP through triazole spacers inC60 tr ZnP tr COOH, and dyadC60 ZnPCOOH did not contain any triazole linker. Photophysical investigation performed by ultrafast transient absorption spectroscopy in solution and on the NiO surface demonstrated that all the porphyrin–fullerene dyads exhibited long-lived charge-separated states due to electron shifts from the reduced porphyrin core to C60 . The transient experiments performed in solution showed that the presence of triazole ring influenced the photophysical properties of the dyadsC60 tr ZnPCOOH andC60 tr ZnP tr COOH and in particular, increased the lifetime of the charge-separated states compared to that of theC60 ZnPCOOH dyad. On the other hand, the corresponding studies on the NiO surface proved that the triazole spacer has a rather moderate impact on the charge separation (NiO–ZnP˙ + –C60 ˙ − ) and charge recombination (NiO– 3 *ZnP–C60 ) rate constants. All three dyads exhibited enhanced performance in terms of photovoltaic measurements with more than threefold increase compared to the reference compoundPh tr ZnPCOOH in which the C60 acceptor is absent. Two different electrolytes were examined (I3 − /I − and Co III/II ) and in most cases, the presence of the triazole ring enhanced their photovoltaic performance. The best performing dyad in I3 − /I − wasC60 tr ZnPCOOH (PCE = 0.076%); in Co III/II, the best performing dyad wasC60 tr ZnP tr COOH (PCE = 0.074%).